Enhancing Nazhir Professionalism through Capacity Building Programs: Evidence from Badan Waqaf Indonesia Medan - Muhammad Fikri Almajid Munthe; Yenni Samri Juliati Nasution; Lailan Syafina (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Waqf has great potential as an instrument of Islamic philanthropy, but its management in Indonesia is still suboptimal. In 2022, the National Waqf Index reached only 0.274, and approximately 10% of waqf assets were managed effectively. This study aims to analyze the influence of Good Waqf Governance and Nazir professionalism on optimizing waqf asset management at the Indonesian Waqf Board (BWI) in North Sumatra. An associative quantitative approach was used, involving 77 Nazirs purposively selected from 335 registered Nazirs. Data were analyzed using multiple linear regression in IBM SPSS 25 after testing for validity, reliability, and classical assumptions. The results indicate that Good Waqf Governance has a positive and significant partial effect on optimizing waqf assets (β = 0.446; sig. = 0.000), as does Nazir professionalism (β = 0.227; sig. = 0.005). Simultaneously, both variables had a significant effect (F = 28.303; sig. = 0.000) with an Adjusted R² of 0.418, meaning that 41.8% of the variation in waqf asset optimization was explained by this model. This finding emphasizes the importance of strengthening the governance system and developing Nazir capacity on an ongoing basis to increase waqf productivity.